Steady-state voltammetry at a microdisc electrode in the absence of excess supporting electrolyte for reversible, quasi-reversible and irreversible electrode kinetics. - Belding, SR; Laborda, E; Compton, R (2012)
The steady-state voltammetry for a one electron reduction, A + e(-) [symbol:see text] B, is studied at a microdisc electrode in the absence of excess supporting electrolyte. For the first time, the full voltammetric waveshape is numerically simulated. Using a combination of theory and experiment, the voltammetry is investigated as a function of two variables: the concentration of the supporting electrolyte and the electrochemical rate constant. The 'hemispherical approximation' (in which a microdisc is assumed to be a hemisphere of 2/π the radius) is shown to be valid under weakly supported conditions, for a range of electrochemical rate constants (K0(r(e))/D(A) = 10(-3) - 10(3)). The simulations were used, in conjunction with the Debye-Hückel theory, to rationalise the experimental steady-state voltammetry of two aqueous redox couples: hexaammineruthenium ([Ru(NH(3))(6)](3+)/[Ru(NH(3))(6)](2+)) and hexachloroiridate ([IrCl(6)](2-)/[IrCl(6)](3-)) (each with varying levels of KCl supporting electrolyte). This investigation provides evidence for ion pairing between [IrCl(6)](2-)/[IrCl(6)](3-) and K(+) from the supporting electrolyte. No observable ion pairing occurs between [Ru(NH(3))(6)](3+)/[Ru(NH(3))(6)](2+) and Cl(-).